Transformable nanosensitizer with tumor microenvironment-activated sonodynamic process and calcium release for enhanced cancer immunotherapy - Tan, Xuan (2022)
Despite the promise of sonodynamic processes in cancer therapy, existing sonosensitizers often fail to regulate the generation of reactive oxygen species (ROS) against tumors, potentially leading to off-target toxicity to normal tissues. We report a transformable core-shell nanosonosensitizer (TiO2 @CaP) that reinvigorates ROS generation and dissolves its CaP shell to release Ca2+ in an acidic tumor microenvironment (TME) under ultrasound activation. Thus, TiO2 @CaP acts as a smart nanosonosensitizer that specifically induces mitochondrial dysfunction via overloading intracellular Ca2+ ions to synergize with the sonodynamic process in the TME. TiO2 @CaP substantially enhances immunogenic cell death, resulting in enhanced T-cell recruitment and infiltration into the immunogenic cold tumor (4T1). In conjunction with checkpoint blockade therapy (anti-PD 1), TiO2 @CaP-mediated sonodynamic therapy elicits systemic antitumor immunity, leading to regression of non-treated distant tumors and inhibition of lung metastasis. This work paves the way to development of "smart" TME-activatable sonosensitizers with temporospatial control over antitumor responses.